Effective Components on the Empowerment of Insured Individuals from the Perspective of Employees of Iran Health Insurance Organization in 2018 - Jalal Saeidpour; Mohammad Javad Kabir; Bahman Khosravi; Moslem Sharifi (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Empowerment of insured persons has been one of the main programs of Iran health insurance organization. Accordingly, this study was designed and implemented with the aim of determining the status of knowledge, attitude and performance of employees, as one of the factors influencing the implementation of the program. Methods: This descriptive-analytic study was carried out in 2016-2018. The data gathering tool was a researcher-made questionnaire that was organized in four sections including demographic information, knowledge, attitude and performance of the staff. The sample size was 1536 people who were selected by random sampling method. Data were analyzed by descriptive (frequency, mean and standard deviation) and analytical (Mann-Whitney, Kruskal-Wallis and correlation tests) methods. Results: A total of 1536 questionnaires were distributed and 1347 questionnaires were received (response rate = 92%). Respondents obtained moderate knowledge score (0.57), desirable attitude (3.9) and moderate performance (1.9). The distribution of the scores in the three main parts of the study showed that the attitude of the staff toward empowerment is positive (73% desirable and 26% moderate). While in the knowledge section, only 43% of the respondents were in desirable condition and 12% were in undesirable condition. In the performance section, only 10% of the respondents had desirable situation and more than 80% showed moderate performance. Conclusion: Positive attitude toward empowerment and its alignment with organizational goals, and weakness in education, and inadequate participation of staff in the design and implementation of programs, are one of the main points that should be considered in designing improvement interventions.